2018
DOI: 10.1111/jocs.13718
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for stroke on left ventricular assist devices

Abstract: Postoperative stroke after LVAD implantation was associated with higher mortality. A history of previous CVA, VTE, and hyperlipidemia were independently associated with stroke while on LVAD support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 18 publications
1
19
0
2
Order By: Relevance
“…The most serious and persistent problem with ventricular assist devices (VADs) is stroke, which has remained relatively constant at a rate of 10‐20% at 2 years . The high complication rates of pulsatile‐flow VADs resulted in the development of electromechanical continuous‐flow (non‐pulsatile) pumps that employ either a centrifugal or axial pump configuration that use electromagnets to spin the central rotors .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most serious and persistent problem with ventricular assist devices (VADs) is stroke, which has remained relatively constant at a rate of 10‐20% at 2 years . The high complication rates of pulsatile‐flow VADs resulted in the development of electromechanical continuous‐flow (non‐pulsatile) pumps that employ either a centrifugal or axial pump configuration that use electromagnets to spin the central rotors .…”
Section: Introductionmentioning
confidence: 99%
“…Other observational studies in recent years have yielded mixed overall results as well . Most recently, Bishawi et al showed a significant decrease in cerebrovascular accidents (CVAs) with centrifugal pumps (23% vs 77%) . Therefore, while the ENDURANCE and Supplemental ENDURANCE trials, Cho's extensive analysis, and numerous other observational reports have added significantly to the understanding of these two LVAD devices, it is difficult to state definitively that one of them is superior to the other in terms of causing debilitating neurologic catastrophes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Last month, Bishawi et al reported the outcomes of stroke in LVAD patients at the Duke University Medical Center . In 390 LVAD patients, 61 patients (15.6%) sustained a stroke while on LVAD therapy.…”
mentioning
confidence: 99%
“…Mechanical thrombectomy has been shown to improve outcomes in patients with strokes on LVAD support and all patients who have suffered an acute stroke should be evaluated for this therapy . Finally, as noted by Bishawi et al, patients who have had a previous stroke or have had or are prone to venous thromboemboli should be carefully screened when selecting candidates for LVAD therapy because of their increased risks for cerebrovascular events. Better patient selection, more aggressive blood pressure control, and anticoagulation control and continued improvements in LVAD technology will be necessary to decrease the incidence of this catastrophic complication.…”
mentioning
confidence: 99%